1991
DOI: 10.1128/aac.35.3.497
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Neisseria gonorrhoeae to cefpodoxime: determination of MICs and disk diffusion zone diameters

Abstract: We studied the susceptibilities of 77 strains of Neisseria gonorrhoeae to four antibiotics: cefpodoxime, ceftriaxone, penicillin, and tetracycline. All strains were susceptible to ceftriaxone. Cefpodoxime MICs (range, 0.001 to 0.125 ,ug/ml) were parallel to and approximately four times those of ceftriaxone, and all strains will probably be considered susceptible to cefpodoxime. Disk diffusion zone diameters for cefpodoxime ranged from 35 to 57 mm. Of the strains, 32% were penicillin resistant and 51% were tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Among the 25 included studies, only four [27] , [28] , [29] , [30] reported all seven of the categories in our data matrix, seven [31] , [32] , [33] , [34] , [35] , [36] , [37] reported data on six of these categories, ten [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] provided information on five of these categories, and four [48] , [49] , [50] , [51] reported data of only four of these categories ( Table 2 ). The quality of an included study was negatively scored in particular when it failed to describe the study population or NG isolate identification method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 25 included studies, only four [27] , [28] , [29] , [30] reported all seven of the categories in our data matrix, seven [31] , [32] , [33] , [34] , [35] , [36] , [37] reported data on six of these categories, ten [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] provided information on five of these categories, and four [48] , [49] , [50] , [51] reported data of only four of these categories ( Table 2 ). The quality of an included study was negatively scored in particular when it failed to describe the study population or NG isolate identification method.…”
Section: Resultsmentioning
confidence: 99%
“…No significant publication bias was found (the Begg rank correlation test, P = 0.197). The susceptibility rate of NG isolates to cefpodoxime was lower than that to cefixime (92.8% vs. 99.8%, χ 2 = 951.809, P<0.001); the former ranged from 89.9% (95% CI: 84.5%–93.5%) to 100% (95% CI: 95.6%–100%) over the five included studies concerning cefpodoxime susceptibility ( Figure 3 ) [27] , [30] , [47] , [50] , [51] . Four reported cefpodoxime susceptibility rates of 100%, and one documented a rate of 89.9%.…”
Section: Resultsmentioning
confidence: 99%
“…Several strains had cefmetazole MICs of .4 ,ug/ml, suggesting that they might not be eradicated with single-dose cefmetazole. To a lesser extent, this has been shown with other cephalosporins such as cefuroxime (75), cefpodoxime (35,93), cefoxitin (75) and even ceftriaxone (50, 102). The very widespread use of cephalosporins could conceivably accelerate the process of selecting less and less 1-lactamsusceptible strains in the way that CMRNG increased slowly in incidence over the decades during which penicillin was the drug of choice for gonorrhea.…”
Section: Cephalosporinsmentioning
confidence: 90%